1996
DOI: 10.1159/000259195
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Induced Cochlear Hypoxia Is Intensity Dependent, Correlates with Hearing Loss and Precedes Reduction of Cochlear Blood Flow

Abstract: Anesthetized and artificially ventilated guinea pigs were exposed to broad-band noise of 95, 101, 106 or 115 dB SPL for 30 min and studied for 180 min after cessation of noise. The partial pressure of oxygen (pO2) in the perilymph, the cochlear blood flow (CoBF) and auditory-evoked potentials were continuously recorded. Arterial blood pressure, electrocardiogram, inspiratory and expiratory gas levels, arterial blood gas levels and acid-base status were kept stable to exclude influences of these para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 21 publications
3
72
0
4
Order By: Relevance
“…26,27 The hypoxic environment induced in the cochlea by noise is immediate and the effects persist after the noise is terminated. 6,28 Studies have shown that when cells encounter low oxygen tension, they adapt by promoting expression of genes associated with anaerobic cell metabolism, cell survival, and angiogenesis. 29 This transcriptional response is mediated by a hypoxia-induc-ible factor (HIF), 30,31 a principal transcription factor, involved in the regulation of transcriptional responses to hypoxia.…”
mentioning
confidence: 99%
“…26,27 The hypoxic environment induced in the cochlea by noise is immediate and the effects persist after the noise is terminated. 6,28 Studies have shown that when cells encounter low oxygen tension, they adapt by promoting expression of genes associated with anaerobic cell metabolism, cell survival, and angiogenesis. 29 This transcriptional response is mediated by a hypoxia-induc-ible factor (HIF), 30,31 a principal transcription factor, involved in the regulation of transcriptional responses to hypoxia.…”
mentioning
confidence: 99%
“…Changes in oxygenation and decreased cochlear blood flow appear to occur first, inducing an accumulation of free radicals in the cochlea that triggers proce and cell death [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Since the auditory hair cells get their oxygen by diffusion, the hypobaric hypoxia present in the cabin of an aircraft during a flight -which typically provides an equivalent pressure of about 2000 to 2300 m -may increase the risk of hearing loss due to noise. The additional risk of hypoxia may contribute to a reduced cochlear capillary perfusion and result in the decrease of perilymphatic oxygen partial pressure induced by the noise [17,18]. Both these effects risk factor for hearing loss.…”
Section: Noise Exposure During Ambulance Flights O R I G I N a L P A mentioning
confidence: 99%